Physical match demand in the FIFA World Cup: An analysis of the 2018 (Russia) and 2022 (Qatar) editions - Dellagrana, R. A.; Pinto, G. M. C.; Santana, H. A. d. P.; Aquino, R. (International Journal of Sports Science & Coaching, 2025)
The 2022 Qatar World Cup was conducted under unique circumstances, setting it apart from previous editions due to schedule and rule modifications. This study aimed to evaluate the physical demand of teams in terms of running disparities between the 2018 and 2022 World Cups. Match performance data were obtained from the official websites of the 2018 Russia World Cup (n = 988 observations) and the 2022 Qatar World Cup (n = 826 observations). Match outcomes included losses (n = 729 player observations), draws (n = 339 player observations), or wins (n = 746 player observations). Players in all positions covered a greater distance during the 2022 World Cup compared to the 2018 edition. When examining the interaction between Cup and Outcome, only total distance covered (F = 5.831, p = 0.003) and distance covered walking (F = 15.488, p < 0.001) showed statistical differences. These findings elucidate that more total distance was covered during draws, with higher values observed in the 2022 World Cup. Thus, the study concludes that the 2022 Qatar FIFA World Cup presented a higher physical match demand compared to the 2018 Russia FIFA World Cup.